Mechanization for scaling from a gender perspective - Kawarazuka, Nozomi (International Potato Center, 2018)
Award presentation given by Nozomi Kawarazuka (CIP) at the Triennial Symposium of the International Society for Tropical Root Crops (ISTRC) which took place between 22-25 October 2018.